Ответ:
Пошаговое объяснение:
пусть второе число будет х
тогда первое число будет 51-х
получаем:
(3/4)x = 2/3*(51-x)
(3/4)x = 34 - (2/3)x
(3/4)x + (2/3)x = 34
(9/12)x + (8/12)x = 34
(17/12)x = 34
x = 34 * 12/17
x = 24 второе число
51-24 = 27 первое число
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Пошаговое объяснение:
пусть второе число будет х
тогда первое число будет 51-х
получаем:
(3/4)x = 2/3*(51-x)
(3/4)x = 34 - (2/3)x
(3/4)x + (2/3)x = 34
(9/12)x + (8/12)x = 34
(17/12)x = 34
x = 34 * 12/17
x = 24 второе число
51-24 = 27 первое число